An Invention without a Future : Essays on Cinema - Naremore, James (Book collections on Project MUSE., 2014)
In 1895, Louis Lumiere supposedly said that cinema is ""an invention without a future."" James Naremore uses this legendary remark as a starting point for a meditation on the so-called death of cinema in the digital age, and as a way of introducing a wide-ranging series of his essays on movies past and present. These essays include discussions of authorship, adaptation, and acting; commentaries on Howard Hawks, Alfred Hitchcock, Orson Welles, Vincente Minnelli, John Huston, and Stanley Kubrick; and reviews of more recent work by non-Hollywood directors Pedro Costa, Abbas Kiarostami, Raúl Ruiz,